Analyses of RANK and RANKL in the post-GWAS context: functional evidence of vitamin D stimulation through a RANKL distal region. - Yoskovitz, G; Garcia-Giralt, N; Rodriguez-Sanz, M; Urreizti, R; Guerri, R; Ariño-Ballester, S; Prieto-Alhambra, D; Mellibovsky, L; Grinberg, D; Nogues, X; Balcells, S; Diez-Perez, A (2013)
Over the past decade, many genome-wide association studies (GWAs) and meta-analyses have identified genes and regions involved in osteoporotic phenotypes. Nevertheless, the large majority of these results were not tested at any functional level. GWA-associated single-nucleotide polymorphisms (SNPs) near candidate genes such as RANK and RANKL suggest that these SNPs and/or other variants nearby may be involved in bone phenotype determination. This study focuses on SNPs along these two genes, which encode proteins with a well-established role in the bone remodeling equilibrium. Thirty-three SNPs, chosen for their location in evolutionary conserved regions or replicated from previous studies, were genotyped in the BARCOS cohort of 1061 postmenopausal women and tested for association with osteoporotic phenotypes. SNP rs9594738, which lies 184 kb upstream of the RANKL gene, was the only SNP found to be associated with a bone phenotype (dominant model: beta coefficient = -0.034, p = 1.5 × 10(-4) , for lumbar spine bone mineral density). Functional experiments exploring a distal region (DR) of 831 bp that harbors this SNP in a centered position (nt 470) demonstrated its capacity to inhibit the RANKL promoter in reporter gene assays. Remarkably, this DR inhibition was significantly reduced in the presence of vitamin D. In conclusion, the GWA-associated SNP rs9594738 lies in a region involved in transcription regulation through which vitamin D could be regulating RANKL expression and bone mineral density.